The Influence of School Principal Supervision and Work Motivation on the Work Discipline of Vocational School Teachers: A Case Study at Public Vocational High School in Batang Regency - Trihandayani, Ifa; Nurkolis, Nurkolis; Haryati, Titik (FKIP - Universitas Riau, 2025)
This study aims to examine the influence of principal supervision and work motivation on teachers’ work discipline at public vocational high schools in Batang Regency. Employing a quantitative approach with a correlational design, the research involved 159 teachers selected through proportional random sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed through descriptive statistics, classical assumption tests, and simple and multiple linear regression analyses. The findings indicate that principal supervision significantly influences teachers’ work discipline, contributing 95.4% to the variance, with follow-up academic supervision being the most dominant dimension. Work motivation also shows a significant influence, contributing 95.8%, where internal motivation emerges as the primary factor. Simultaneously, principal supervision and work motivation contribute 95.8% to teachers’ work discipline, with time discipline as the leading dimension. This research offers novelty by mapping the contribution of each dimension of the studied variables in a specific context rarely explored quantitatively. The study is limited to public vocational schools within one district and relies on self-reported data, which may involve subjectivity. Future research is recommended to expand the scope, apply mixed-methods designs, and include mediating or moderating variables such as transformational leadership or school culture to gain deeper insights.